Answers

2015-09-10T21:33:38+05:30
[1+(cosФ/sinФ)-(1/sinФ)] [1+(sinФ/cosФ)+(1/cosФ)]         (∵cotФ=cosФ/sinФ )                                                                                                             (∵tanФ=sinФ/cosФ)
                                                                                    (∵cosecФ=1/sinФ)
                                                                                    (secФ=1/cosФ)
[(sinФ+cosФ)-1]/sinФ [(cosФ+sinФ)+1]/cosФ               (∵(a-b) x (a+b) =a²-b² )

[(sinФ+cosФ)²-1²]/sinФ.cosФ

[sin²Ф+cos²Ф+2sinФ.cosФ-1]/sinФ.cosФ

[1+2sinФ.cosФ-1]/sinФ.cosФ

2sinФ.cosФ/sinФ.cosФ

2


2 3 2